Reaganomics: Pragmatic or Ideological, Revolution or Reform, Success or Failure? (Global Journal of Management and Business Research, 2023)
P resident Ronald Reagan s ideology posited that it was the government that caused persistent poverty and that welfare had to be rolled back to incentivize people to work Obviously something is desperately wrong with our welfare system we spend vast amounts on a system that perpetuates poverty But the waste of money pales before the sinful waste of human potential - the squandering of so many millions of hopes and dreams President Reagan wanted to roll back the welfare state deregulate the economy and incentivize private business to be the primary driver of economic growth so he embraced a new conservative school of economic thought Supply-Side Economics Although Reagan s adoption of Supply-Side Economics in the 1980s was originally ideologically driven as an anti-Keynesian and anti-New Deal policy that was meant to lessen the scope of government control over the economy Reagan quickly became pragmatic in order to address the economic problems at hand especially stagflation in turn failing in many ways at his ideological goal of lessening government intervention in the economy